Development of a current mirror-integrated pressure sensor using CMOS-MEMS cofabrication techniques. Issue 4 (1st October 2018) - Kumar, Shashi; Rathore, Pradeep Kumar; Panwar, Brishbhan Singh; Akhtar, Jamil
Abstract : Purpose: This paper aims to describe the fabrication and characterization of current mirror-integrated microelectromechanical systems (MEMS)-based pressure sensor. Design/methodology/approach: The integrated pressure-sensing structure consists of three identical 100-µm long and 500-µm wide n -channel MOSFETs connected in a resistive loaded current mirror configuration. The input transistor of the mirror acts as a constant current source MOSFET and the output transistors are the stress sensing MOSFETs embedded near the fixed edge and at the center of a square silicon diaphragm to sense tensile and compressive stresses, respectively, developed under applied pressure. The current mirror circuit was fabricated using standard polysilicon gate complementary metal oxide semiconductor (CMOS) technology on the front side of the silicon wafer and the flexible pressure sensing square silicon diaphragm, with a length of 1, 050 µm and width of 88 µm, was formed by bulk micromachining process using tetramethylammonium hydroxide solution on the backside of the wafer. The pressure is monitored by the acquisition of drain voltages of the pressure sensing MOSFETs placed near the fixed edge and at the center of the diaphragm. Findings: The current mirror-integrated pressure sensor was successfully fabricated and tested using in-house developed pressure measurement system. The pressure sensitivity of the tested sensor was found to be approximately 0.3 mV/psi (or 44.6 mV/MPa) for pressure range of 0 to 100 psi. In addition, the pressure sensor was also simulated using Intellisuite MEMS Software and simulated pressure sensitivity of the sensor was found to be approximately 53.6 mV/MPa. The simulated and measured pressure sensitivities of the pressure sensor are in close agreement. Originality/value: The work reported in this paper validates the use of MOSFETs connected in current mirror configuration for the measurement of tensile and compressive stresses developed in a silicon diaphragm under applied pressure. This current mirror readout circuitry integrated with MEMS pressure-sensing structure is new and fully compatible to standard CMOS processes and has a promising application in the development CMOS-MEMS-integrated smart sensors.